Professional health: obesity status and 24-hours diet recall of health-staff working at selected three primary care clinics in Kuantan, Malaysia - Tin, Myo Han; Md Aris, Mohd Aznan; Mohd Shukri, Nor Azwani; Osman, Iskandar Firzada; Thuraiapprah, Mahendran; Abdullah, Fa’iza; Sahrin, Saidatul Nabila; Ismail, Nur Athirah; Mazubir, Nizatul Nuraih (2016)
Obesity statistics in Malaysia rank sixth with highest adult obesity rate in Asia. Therapeutic Lifestyle-Change diet (TLC-Diet) is advised by health-practitioners to over-weight/obese patients as one component of lifestyle modification therapy. However, there is limited data on obesity-status and diet-patterns among health-practitioners who are dealing with obese-patients in primary-care.